Analisis Pengembangan Perangkat Lunak Berbasis AI (Gemini) Menggunakan Penerapan ACM Code of Ethics - Rexcy Elsan; Andi Lala; RG. Guntur Alam (JSAI (Journal Scientific and Applied Informatics), 2025)
This research aims to analyze the application of the ACM Code of Ethics in the development of AI Gemini software by Google DeepMind. With the development of artificial intelligence (AI) technology, developers need to pay attention to ethical aspects in every stage of system development. This research uses a qualitative approach with a data triangulation method, which includes document analysis, interviews with AI experts, and a literature study. The results show that although Gemini AI has complied with some key ethical principles in the ACM Code of Ethics, such as data security and privacy (90%) and human well-being (85%), there are still challenges related to transparency (60%) and bias mitigation (70%). Lack of transparency in algorithms and training data as well as potential bias in results generated by AI are the main issues that need to be improved. Based on the results, overall the Gemini AI has shown fairly good ethical compliance with an average of 76.67% but still requires improvement in the aspects of transparency, bias mitigation, and usage regulation.